The Representation of Women in the Film Ipar Is Death Critical Discourse Analysis of Sara Mills - Dina Sari Hardiyanti Lutfi Fadilla; Anwar Efendi; Zamzani (Britain International for Academic Research (BIAR) Publisher, 2024)
Talking about women's issues is very embedded in society, so it is difficult for women to escape from the labels attached to them. Injustice causes feminism to fight for women's rights. This method focuses on feminist discourse displayed in image text and news. The aim of this research is to determine the subject-object position and the reader's position. The method used in this research is descriptive qualitative with a critical discourse analysis approach modeled by Sara Mills, the characters Nissa and Rani have the image of a wife who is obedient to her husband and successful in life having to face storms in her household caused by her husband and Rani. This analysis focuses on the depiction of women shown in the film Ipar as death. Therefore, what Sara Mills does is often also referred to as a feminist perspective. The point of attention from a feminist discourse perspective is showing how texts are biased in presenting women as those who are in the wrong.